Clostridium difficile and cytotoxin in routine faecal specimens. - Nash, J Q (1982)
Over a five-month period 1239 unselected, routine faecal specimens from 856 patients were examined for Clostridium difficile. One hundred specimens representing 69 patients were culture-positive. Toxin was detected in the stool of ten. During the study period, there were 41 Salmonella, 12 Campylobacter and 9 Shigella infections. C difficile was isolated together with Salmonella from 12 patients. No patient required specific treatment for C difficile infection. The significance of these findings is discussed.